Identity construction through online luxury consumption among young consumers - Karanapakorn, Varisara (2016)
Social media has recently become an integral part of daily lives among individuals around the world. With this digital innovation, people have changed the way they consume products, express their identities, and communicate with each other. This study investigates how consumers construct identity through luxury consumption in an online context; particularly, Facebook. Most extant research papers explore the identity construction through anonymous context such as virtual game world; in contrast, Facebook is considered as a non-anonymous context because people are established by their real names and pictures. The author explores how participants manage their online presentation of self and investigates the goal or values that customers seek from presenting the use of luxury product online in Thailand, which is regarded to have a top number of Facebook users and also one of the highest levels of luxury expenditure in Asia. The qualitative research was conducted on a convenience sample of ten Thai participants whose age ranged from 20-25 years who are users of Facebook and have prior luxury consumption. The result indicates that people are more susceptible to interpersonal influences. The majority of people on Facebook use the display of luxury to signal status and power as well as to seek friendship and compliance. They tend to strategically manage their profiles through the highly visible luxury consumption. Wealth signals are seen as appropriate in Thai context because they provide many social benefits such as enhancing one's appearance and social recognition. People feel self-enhanced through seeking affirmations and likes from friends and they account on the number of likes and comments. With the lack of richness of interaction in the online context, people tend to hide certain aspects of self and instead construct a desired aspect of self. However, due to the honest characteristic of Facebook, they tend to present a favourable self within the bounds of reality.